AB1224-HPR Could we use the lay referral system to improve the early arthritis clinic efficiency?. (15th June 2017) - Dobroiu, M; Trandafir, M; Ioan, C; Vasile, D; Predeteanu, D; Ionescu, R; Berghea, F; ,
Abstract : Background: The professional's monopoly on knowledge about disease and its treatment is something gone now, in the era of internet and patient consumerism. In addition, the interest of rheumatologists (and the interest of the society, too) shifted toward early recognition of the disease and early arthritis clinics. Education is definitely one of the solutions to increase the awareness of potential patients regarding rheumatic diseases. However most of rheumatic diseases are not very frequent in the population that raise the problem of cost efficacy of the education process. Per Eliot Freidson's view, the members of every community of whatever kind share some cultural understandings about disease, treatment, and cure. The lay community network could be considered an instrument for dissemination of proper knowledge regarding health and could help to earlier recognition of a sign of disease related to early arthritis. Objectives: To identify the opportunity of using lay network for early arthritis referral. In addition, we intended to identify the most suitable vectors from this network to be used for education and dissemination of medical knowledge. Methods: 48 rheumatic patients (mean age (SD): 50.8 (14, 7)) consecutively admitted in one tertiary clinic have been invited to answer to a structured questionnaire. Sex ratio (M: F) was 1:2, average disease duration 7.7 (8.3) years. Results: In 28.3% cases the first sign of disease was noticed not by the patient but by somebody else, for 36.7% a delay of several months to one year was declared between first sign of disease and professional examination, 71.7% use to discuss bout health problems with their lay network (often and very often), 76.1% consider them able to give pertinent advices regarding the disease they suffer from, 45, 7% are ready to act as an education vector and 41, 3% are ready to participate in additional education programs. They interest in such activity is not related to gender, education level or work status. Conclusions: Lay network referral could be a powerful instrument to reduce the duration between onset of rheumatic symptoms and medical visit, to increase the awareness regarding rheumatic disease, to reduce the cost of health education. Health professionals should understand how to use these networks. References: Freidson, Eliot. 1960. "Client Control and Medical Practice." American Journal of Sociology 65:374–82. Barley, Stephen R., and Gideon Kunda. 2004. Gurus, Hired Guns, and Warm Bodies: Itinerant Experts in a Knowledge Economy. Princeton, NJ: Princeton University Press. Disclosure of Interest: None declared